Allgemeine Ziele des Mathematikunterrichts eingebettet in ein ganzheitliches Konzept von Menschenbildung: Theoretische Erörterungen und beispielhafte Erläuterungen (mathematica didactica, 2021)
The acquirement of seperate competences does not compose a general education (Bildung) for school. This will be explained first followed by citations from the 1970th where it is worked out that a simple deduction of special and contend orientated objectives out of general aims is not possible. A back coupling to a concept of education (Bildung) therefore is advisable. The conceptual design of general education (Allgemeinbildung) producedby W. Klafki in 1985 is taken as example for this. Following Klafki and some own preliminary studies the author developed a conception of general education for mathematics education in the end of the 1980th and the beginning of the 1990th; the hereby developed fourdimensions of general education in mathematics education will be presented here. In the scope of such a conception the competences you know from the German standards of education for mathematic teaching can be helpful but in this context here they are not singular standing axioms of didactics. In the second part of the paper three exemplary themes (out of the domains Arithmetic, Geometry, Application) will be described and discussed in respectto general aims.